(untitled) (Dhaka University Journal of Science, 2016)
This paper deals with minimizing average of loss functions using Gradient Descent (GD) and Stochastic Gradient Descent (SGD). We present these two algorithms for minimizing average of a large number of smooth convex functions. We provide some discussions on their complexity analysis, also illustrate the algorithms geometrically. At the end, we compare their performance through numerical experiments. Dhaka Univ. J. Sci. 64(2): 141-145, 2016 (July)